Alterations in lipid and carbohydrate metabolism attributable to cyclosporin A in renal transplant recipients. Issue 6512 (4th January 1986) - Harris, K P; Russell, G I; Parvin, S D; Veitch, P S; Walls, J
Abstract : Thirteen non-diabetic renal transplant recipients had various aspects of carbohydrate and lipid metabolism studied before and after conversion from cyclosporin A to azathioprine. No patient had a glucose tolerance test result diagnostic of diabetes mellitus before conversion, and there was no change in fasting glucose or immunoreactive insulin values after conversion. There was, however, a fall in the area under the curve of the glucose tolerance test values after conversion. Furthermore, fasting serum cholesterol and triglyceride concentrations fell significantly after conversion. No change in the concentration of high density lipoprotein cholesterol was detected. These findings suggest that cyclosporin A is associated with an inferior lipid profile as compared with azathioprine, which may be important in patients with transplants given the drug long term.